FTIR spectral changes in Candida albicans biofilm following exposure to antifungals - Alya Nur Athirah Kamaruzzaman,; Tengku Elida Tengku Zainal Mulok,; Nurul Hidayah Mohamad Nor,; Mohd Fakharul Zaman Raja Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Candida albicans is a microbial fungus that exists as a commensal member of the human microbiome and an opportunistic pathogen. Biofilm formation by this fungal pathogen occurs mostly in the mucosa or endothelium associated with candidiasis and colonizes medical devices. The present work was performed to determine the efficacy of the antifungal creams on the viability and biochemical composition of C. albicans biofilm. Four commercial antifungal creams were used herein namely econazole nitrate, miconazole nitrate, ketoconazole and tolnaftate. Resazurin assay and Fourier transform infrared (FTIR) spectroscopy were performed to determine the viability and biochemical composition of C. albicans biofilm, respectively. Results demonstrated that the antifungal creams inhibited C. albicans biofilm. The highest percent inhibition shown by econazole nitrate, miconazole nitrate, ketoconazole, and tolnaftate were 16.5%, 17.1%, 15.8%, and 6.9%, respectively. Econazole nitrate with the lowest IC50 value of 43.42 μg/mL caused changes in the FTIR spectral peak shape at 1377 cm-1 and 1736 cm-1. On the other hand, miconazole nitrate with the second lowest IC50 value of 118.26 μg/mL caused spectral peak shifting from 1237 cm-1 to 1228 cm-1. In conclusion, the inhibition of C. albicans biofilm may be mediated by the changes in protein, lipid, and nucleic acid compositions.